Taxation and development: A review of donor support to strengthen tax systems in developing countries - Odd-Helge Fjeldstad (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Recent years have seen a growing interest among donors on taxation in developing countries. This reflects a concern for domestic revenue mobilization to finance public goods and services, as well as recognition of the centrality of taxation for growth and redistribution. The global financial crisis has also led many donor countries to pay more attention to the extent and effectiveness of the aid they provide, and to ensuring that they support rather than discourage the developing countries' own revenue-raising efforts. This paper reviews the state of knowledge on aid and tax reform in developing countries, with a particular focus on sub-Saharan Africa. Four main issues are addressed: (1) impacts of donor assistance to strengthen tax systems, including what has worked, or not, and why; (2) challenges in 'scaling up' donor efforts; (3) how to best provide assistance to reform tax systems; and (4) knowledge gaps to be filled in order to design better donor interventions. The paper argues that donors should complement the traditional 'technical' approach to tax reform with measures that encourage constructive engagement between governments and citizens over tax issues.
Keywords: F35; H20; O23; 330; tax policy; tax administration; tax effort; technical assistance; Steuerpolitik; Finanzverwaltung; Steuereinnahmen; Entwicklungshilfe; Entwicklungsländer